SUITABILITY OF ELECTRICAL CONDUCTIVITY TESTING AND ACCELERATED AGING FOR EVALUATING THE VIGOR OFCITHAREXYLUM MYRIANTHUM CHAM. DIASPORES - Bazzanella, Ana Paula; Mathias, Gabriele Larissa; Gattermann Mittelstaedt, Henrique Roberto; Ribeiro, Maiara Iadwizak; Teixeira Forte, Andréa Maria; Corsato, Jaqueline Malagutti (Floresta, 2019)
The Atlantic Forest is one of the most threatened Brazilian biomes by anthropic action. Thus, the interest inrecovering degraded areas through the use of native tree species has increased, causing a high demand in the use of vigorous seeds. This research aimed at evaluating the suitabilityof the electrical conductivity and accelerated aging tests to evaluate the vigor of C. myrianthum diaspores. For the adequacy of the electrical conductivity test, a completely randomized experimental design (CRD) was used in a 2 x 3 x9 (number of diaspores x volume of water x imbibition time)at a constant temperature of 25 °C. The procedure for the accelerated aging test was conducted at 40 ºC for 0 (no aging), 24, 48 and 72 hours. ACRDwas also used for the accelerated aging test, totaling 4 treatments. The results were submitted to analysis of variance (ANOVA) and the means were compared by the Tukey test at 5% probability. It is concluded that the electrical conductivity test for C. myrianthum diaspores can be conducted with 25 diaspores soaked with 50 mL of deionized water for 96 hours, thus replacing the germination test with the advantage of being carried out in a shorter period of time. Moreover,the 24 and 48 hour accelerated aging period is adequate to discriminate the vigor of C. myrianthum diaspores, with GSI and MGT being the most sensitive variables.